The FRESH study: treatment of intracranial aneurysms with the new FRED X flow diverter with antithrombotic surface treatment technology - first multicenter experience in 161 patients - Vollherbst, Dominik; Lücking, H.; DuPlessis, J.; Sonnberger, M.; Maurer, C.; Kocer, N.; Killer-Oberpfalzer, M.; Rautio, R.; Valvassori, L.; Berlis, A.; Gasser, S.; Gatt, S.; et al. (American journal of neuroradiology, 2023)
BACKGROUND AND PURPOSE: Flow diverters with antithrombotic coatings are increasingly used to improve the safety of flow diverter treatments of intracranial aneurysms. This study aimed to investigate the safety and short-term efficacy of the new FRED X flow diverter. - MATERIALS AND METHODS: Medical charts and procedural and imaging data of a consecutive series of patients with intracranial aneurysms who were treated with the FRED X at 9 international neurovascular centers were retrospectively analyzed. - RESULTS: One hundred sixty-one patients (77.6% women; mean age, 55 years) with 184 aneurysms (11.2% acutely ruptured) were included in this study. Most aneurysms were located in the anterior circulation (77.0%), most frequently at the ICA (72.7%). The FRED X was successfully implanted in all procedures. Additional coiling was performed in 29.8%. In-stent balloon angioplasty was necessary in 2.5%. The rate of major adverse events was 3.1%. Thrombotic events occurred in 7 patients (4.3%) with 4 intra- and 4 postprocedural in-stent thromboses, respectively (1 patient had both peri- and postprocedural thrombosis). Of these thrombotic events, only 2 (1.2%) led to major adverse events (ischemic strokes). Postinterventional neurologic morbidity and mortality were observed in 1.9% and 1.2%, respectively. The rate of complete aneurysm occlusion after a mean follow-up of 7.0 months was 66.0%. - CONCLUSIONS: The new FRED X is a safe and feasible device for aneurysm treatment. In this retrospective multicenter study, the rate of thrombotic complications was low, and the short-term occlusion rates are satisfactory.
Gesehen am 06.06.2023